2021
DOI: 10.1186/s13024-021-00433-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered network properties in C9ORF72 repeat expansion cortical neurons are due to synaptic dysfunction

Abstract: Background Physiological disturbances in cortical network excitability and plasticity are established and widespread in amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) patients, including those harbouring the C9ORF72 repeat expansion (C9ORF72RE) mutation – the most common genetic impairment causal to ALS and FTD. Noting that perturbations in cortical function are evidenced pre-symptomatically, and that the cortex is associated with widespread pathology, cortical dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 66 publications
3
43
0
Order By: Relevance
“…Pre-symptomatic and early-symptomatic changes in cortical dendritic spines, neuromuscular junctions and the synaptic inputs to spinal cord MNs have all been reported (Fogarty et al, 2015(Fogarty et al, , 2016Perkins et al, 2021;Sasaki & Iwata, 1995;Starr & Sattler, 2018;Tremblay et al, 2017;Van Zundert et al, 2008). Separate evidence indicates that astrocytes, the supportive glial cells of the CNS, may be responsible for non-cell autonomous degeneration of MNs (Devlin et al, 2015;Forsberg et al, 2011;Valori et al, 2014;Yamanaka et al, 2008;Yamanaka & Komine, 2018;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-symptomatic and early-symptomatic changes in cortical dendritic spines, neuromuscular junctions and the synaptic inputs to spinal cord MNs have all been reported (Fogarty et al, 2015(Fogarty et al, , 2016Perkins et al, 2021;Sasaki & Iwata, 1995;Starr & Sattler, 2018;Tremblay et al, 2017;Van Zundert et al, 2008). Separate evidence indicates that astrocytes, the supportive glial cells of the CNS, may be responsible for non-cell autonomous degeneration of MNs (Devlin et al, 2015;Forsberg et al, 2011;Valori et al, 2014;Yamanaka et al, 2008;Yamanaka & Komine, 2018;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“… Benussi et al (2016) predict that synaptic/network plasticity impairments present 15 years before symptomatic onset making these pathological observations some of the earliest evidenced in ALS-FTD patients. Direct evidence of impaired synaptic potentiation of mini excitatory post-synaptic currents was recently confirmed in induced pluripotent stem cell (iPSC)-derived cortical neurons generated from C9ORF72 RE patients, a feature that was rescued in isogenic, gene-corrected lines ( Perkins et al, 2021 ). Beyond this, functional investigations of impaired synaptic plasticity in ALS and FTD have been determined in hippocampal murine preparations: UBQLN2 P 497 H ( Gorrie et al, 2014 ); SOD1 G 93 A ( Spalloni et al, 2011 ) and TDP-43 transgenic mice ( Koza et al, 2019 ), TDP-43 conditional knockout mice ( Wu et al, 2019 ).…”
Section: Cortical Dysfunction In C9orf72 Repeat Expansion-mediated Amyotrophic Lateral Sclerosis-frontotemporal Dementmentioning
confidence: 93%
“…Excitatory neurons represent approximately 80% of the adult cortex and numerous pieces of evidence are converging toward the contribution of these neurons to abnormalities in cortical excitability in ALS-FTD patients. Perkins et al (2021) demonstrated that cultures of excitatory cortical neurons derived from C9ORF72 RE iPSCs displayed an enhanced network burst frequency compared to control derived neurons. These properties appear to be explained by the fact that C9ORF72 RE excitatory neurons had an increased functional synaptic input due to increased synaptic density, but not altered intrinsic excitability.…”
Section: Cortical Dysfunction In C9orf72 Repeat Expansion-mediated Amyotrophic Lateral Sclerosis-frontotemporal Dementmentioning
confidence: 97%
See 2 more Smart Citations